Optimisation of supercritical fluid extraction of orange (Citrus sinenis L.) peel essential oil and its physicochemical properties - Ling, Felicia Wen Xia; Kobun Rovina; Nasir Md Nur Aqilah; Abdul Aziz Jaziri (Elsevier B.V., 2024)
In this study, the choice of supercritical fluid extraction as a renewable alternative for extracting orange peel essential oil (OPEO) was motivated by concerns about sustainability with conventional solvent extraction methods. The physical and chemical characteristics of OPEO were examined to assess its potential as a sustainable resource. The extraction process was optimised, and the ideal conditions determined were 317.51 min of extraction time at 74.85 °C with a solvent-to-sample ratio of 4. Analysis of the extracted OPEO revealed significant values for saponification (121.67 mg KOH/g), acid (4.13 mg KOH/g), ester (117.54 mg KOH/g), and free fatty acid (1.56 mg KOH/g) content, demonstrating its composition. Notably, key ingredients such as Limonene (43.96%), α-pinene (15.60%), β-myrcene (10.21%), γ-terpinene (5.00%), and α-terpineol (4.15%) were found in high proportions according to chemical composition analysis. Furthermore, OPEO exhibited excellent antioxidant properties with an IC50 value of 7.73 ± 2.00 mg/mL and displayed notable antimicrobial activity against various microorganisms, including P. aeruginosa (17.7 ± 0.6 mm), E. coli (11.0 ± 0.0 mm), K. pneumoniae (10.7 ± 0.6 mm), and S. aureus (10.3 ± 0.6 mm). These findings have significant implications for the flavor and fragrance sector, as well as for the food preservation industry.